2003
DOI: 10.1111/j.1469-8749.2003.tb00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor, cognitive, and behavioural disorders in children born very preterm

Abstract: Children born preterm have been shown to exhibit poor motor function and behaviour that is associated with school failure in the presence of average intelligence. A geographically determined cohort of two‐hundred and eighty preterm children (151 males, 129 females) born before 32 weeks’gestation and attending mainstream schools were examined at 7 to 8 years of age together with 210 (112 males, 98 females) age‐ and sex‐matched control participants were tested for motor, cognitive, and behavioural problems. Test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
102
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(116 citation statements)
references
References 22 publications
(13 reference statements)
8
102
1
5
Order By: Relevance
“…2 Movement and motor coordination are critical components of development, aiding functions such as learning to sit and eating in infancy, to playing with friends at kindergarten, and handwriting at school. 3 Perinatal complications such as low birthweight, gestational age, brain injury, and postnatal corticosteroids have all been associated with poorer motor outcomes in very preterm infants. 4 However, these perinatal complications do not account for all of the variance in motor outcomes, and other methods for identifying those children most at risk are required.…”
mentioning
confidence: 99%
“…2 Movement and motor coordination are critical components of development, aiding functions such as learning to sit and eating in infancy, to playing with friends at kindergarten, and handwriting at school. 3 Perinatal complications such as low birthweight, gestational age, brain injury, and postnatal corticosteroids have all been associated with poorer motor outcomes in very preterm infants. 4 However, these perinatal complications do not account for all of the variance in motor outcomes, and other methods for identifying those children most at risk are required.…”
mentioning
confidence: 99%
“…Infants born with ELBW have a 20-25 % incidence of these disabilities (Halsey et al 1996; Bennett and Scott 1997;Aylward 2005), whereas full-term-born infants have a 5 % incidence (Paneth 1995). Other common disorders that might be difficult to detect before school age are learning disorders, attention deficiency hyperactivity disorder (ADHD), behavioral problems, sensory and motor system underdevelopment and reduced muscle strength (Samsom et al 2002;Foulder-Hughes and Cooke 2003). It has been estimated that as many as 50-70 % of infants born ≤1500 g (VLBW) suffers one or several dysfunctions of a severity that tends to increase with smaller birth weight (O'Callaghan et al 1996; Goyen et al 1998; Taylor et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Follow up studies have shown that infants born very preterm with very low birth weight (VLBW) are at high risk of cerebral palsy (CP) and other developmental deficits [2][3][4][5] . Although not all premature infants and LBW infants develop disabilities or deficits, they may have problems, such as tension imbalance or inappropriate joint motion range and movement, or experience developmental delays due to immature regulation of alertness and improper automatic postural response 6) .…”
Section: Introductionmentioning
confidence: 99%